A Study on the Effectiveness of Face-to-face Physical Therapy and Non-face-to-face Physical Therapy in Individuals With Rounded Shoulder - Young-ji Cho; Min-je Kim; Cho-won Park; Ye-bin Cho; In-A Heo; Su-jin Kim (Korean Research Society of Physical Therapy, 2023)
Background: This study was carried out to determine whether non-face-to-face physical therapy would have similar exercise effects to face-to-face physical therapy. Hence, we developed an approach for patients, unable to visit hospitals due to circumstances such as the COVID-19 pandemic, to conduct physical therapy comfortably at home. Objects: This study aimed to compare the effects of a face-to-face and a non-face-to-face physical therapy treatment on improving a rounded shoulder posture. Methods: The participants with rounded shoulders were randomly divided into a face-toface group (n = 15) and a non-face-to-face group (n = 15), and each group performed exercises for four weeks. The exercise program consisted of the bare hands exercise, Thera-Band exercise, and foam roller exercise. The participants in the face-to-face group came to a designated place to perform their exercises, and those in the non-face-to-face group performed the exercises at their own home using Google Meet (Google). Acromial height, total scapular distance (TSD), shoulder pain and dysfunction index (SPADI), and pectoralis minor thickness were measured. Data analysis was performed using the R Statistical Software (R Core Team), and a normality test was performed using the Shapiro-Wilk test. Results: There were no significant differences between the face-to-face and the non-face-toface groups (p > 0.05). When comparing the differences before and after the exercises, both the face-to-face and the non-face-to-face groups showed significant differences in acromial height, SPADI, and pectoralis minor thickness (p < 0.05), and both groups showed no significant difference in TSD before and after the exercises (p > 0.05). Conclusion: The results of this study support the results of previous studies reporting that shoulder stabilization exercise and pectoralis minor stretching training improves round shoulders. In addition, this study revealed that both the face-to-face and the non-face-to-face physical therapy treatments had therapeutic effects.